KARAKTERISTIK GENDER KEBIJAKAN PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI ASEAN INDONESIA - Diah Ayu Intan Sari; Bagus Sigit Sunarko; Honest Dody Molasy (Journal of Feminism and Gender Studies, 2021)
The Indonesian government’s effort to protect Indonesian migrant workers abroad began after Indonesia ratify a policy to protect migrant workers as outlined in Law Number 39 of 2004, but the existence of this policy did not necessarily reduce the number of violence against Indonesian migrant workers abroad during the presidency of President Susilo Bambang Yudhoyono. The purpose of this research is to analyze the characteristics of the protection policy for Indonesian migrant workers during the presidency of President Joko Widodo using the concept of Ethics of Care by Carol Gilligan and to analyze the gender character of Indonesia as a sending country in relation to the recipient countries of migrant workers in the protection policy of Indonesian migrant workers within ASEAN through gender perspective. The research uses a qualitative method. The results of this study indicate that the characteristics of Indonesian political policies in the effort to protect Indonesian migrant workers in legal form is quite feminine because there are values ​​of concern and caring for migrant workers in Law number 19 of 2017, but in practice the absence of derivative regulations to realize the mandate of the law causes an old pattern happen in the reality so that the characteristics of migrant worker protection policies that have occurred todays are still masculine. Meanwhile, the gender character of Indonesia as a sending country for migrant workers that is subordinated by the receiving country and does not have the ability to protect its migrant workers shows a feminine gender character of Indonesia because in its interactions with receiving countries in ASEAN, Indonesia is considered weak because it does not have bargaining power in protection efforts to its migrant workers abroad.